Help Your Kids with English : A Unique Step-by-Step Visual Guide - Vorderman, Carol (London Dorling Kindersley, 2013)
This title offers a simple, visual guide to helping children understand English from Carol Vorderman. Reduce the stress of studying English and help your child with their homework by following "Help Your Kids with English", a unique visual guide that demystifies the subject for everyone. Carol Vorderman uses clear, accessible pictures, diagrams and easy-to-follow step-by-steps to cover all the important areas including punctuation, grammar, spelling, and communication skills, so you can approach even the most complex English concepts with confidence. It includes cross-references throughout to show links between language ideas and a glossary of key terms. "Help Your Kids with English" is the perfect guide for every frustrated parent and desperate child, who wants to understand English and put what they've learnt into practice.
Include Color Illustration and Index
Keywords: English language -- Language acquisition--Parent participation